Grain Refinement with Remarkable Basal Texture of Hot-Dipped Zn-Al-Mg Alloy Coating on a Steel Sheet: Evidence of Dendrite Fragmentation - Park, Dong-Jae; Choi, Jihun; Kim, Tae-Chul; Kim, Dong-Ik; Kim, Myung-Soo; Huh, Joo-Youl (대한금속·재료학회, 2023)
Hot-dip galvanized (HDG) Zn-1.7Al-1.4 Mg (wt%) coatings were fabricated on a steel sheet with an increased after-pot cooling rate. Microstructure and microtexture analyses showed that the primary Zn phase in the coatings exhibited a fine-grained equiaxed microstructure with an extremely sharp basal texture (similar to 1630 x random). The increased after-pot cooling rate induced the primary Zn phase to nucleate within the undercooled coating layer, away from the steel substrate. This study provides evidence that the fine equiaxed Zn grains originated from the fragmentation of primary Zn dendrites prior to binary and ternary eutectic solidification, which was previously unknown for HDG coatings. The sharp basal texture of the refined Zn grains indicates that all primary Zn dendrites, prior to their fragmentation, were aligned with their crystallographic c-axes parallel to the coating plane normal. We propose that the primary Zn dendrites, which initially nucleated with random orientations, rotate into the final orientations as their primary arms grow along the < 10 (1) over bar0 > directions and impinge on the substrate or melt surface. The results of the present study provide further insights into the microstructural modification of HDG Zn-Al-Mg alloy coatings by controlling the hot-dip processing parameters.